On the Interpretation and Use of Mediation: Multiple Perspectives on Mediation Analysis - Agler, Robert; De Boeck, Paul (Frontiers in Psychology, 2017)
Mediation analysis has become a very popular approach in psychology, and one that is associated with multiple perspectives that are often at odds despite each serving to address particular problems. Explicitly discussing these perspectives and their motivations, advantages, and disadvantages can help to clarify problems and discussions associated with the use and the refinement of mediation models. We discuss five different perspectives on mediation analysis, their associated advantages and disadvantages, and their implications: with vs. without a mediation hypothesis, effect-focused vs. model-focused, directness vs. indirectness of causation, effect size vs. null hypothesis testing, and hypothesized vs. alternative explanations. Some philosophical and linguistic considerations are briefly discussed, as well as some other perspectives we do not develop here.